Vocabulary Mastery of Students Who Play Mobile Legends Game at Eleventh Grade of MAN 2 Lombok Timur Academic Year 2022/2023 - Sani, Rabiul; Baharuddin; Apgrianto, Kurniawan; Melani, Boenista Zulanda (Program Studi Pendidikan Bahasa Inggris, 2024)
The aim of the study is to determine the level of students’ specific vocabulary mastery on mobile legends. This study analyzed specific vocabulary mastery of students who play mobile legends of the 11 grade students of MAN 2 Lombok Timur. Descriptive quantitative method was used in this study and the population was 19 students and all of the population was taken as the sample. The data were collected by conducting a test. The test consisted of 30 questions and there are tree aspects of vocabulary in the test, i.e., word form, meaning and use aspect. The result of this study shows that student’s mean score is 72.26, median is 71, mode is 87 and standard deviation is 12.60. Based on the test result, student’s achievement score is classified as good. Among 19 students, 5 were classified as very good, 10 as good, 3 as fair, 1 as poor, and none as very poor in vocabulary mastery. The test covered three aspects: word form, meaning, and use. In word form, 9 students were very good, 6 good, and 4 poor, with a mean score of 6.78 and standard deviation of 2.41. For meaning, 9 were very good, 7 good, and 3 fair, with a mean of 16.57 and standard deviation of 3.92. In usage, 1 student was very good, 14 good, 3 fair, and 1 poor, with a mean of 48.89 and standard deviation of 8.29. Overall, the students' vocabulary mastery was classified as good. It can be concluded that students who play mobile legends have good specific vocabulary mastery on mobile legends based on the test results that have been obtained as can be seen that the average student score is good with an average score of 72.26, which is a good score.